Mapping and characterization of dominant hydrolase enzymes in the digestive tract of Striped marlin (Kajikia audax Philippi, 1887) - ENDANG ISMAIL; ASEP AWALUDIN PRIHANTO; SUKOSO SUKOSO; HARTATI KARTIKANINGSIH (Society for Indonesian Biodiversity, 2025)
Abstract. Ismail E, Prihanto AA, Sukoso, Kartikaningsih H. 2025. Mapping and characterization of dominant hydrolase enzymes in the digestive tract of Striped marlin (Kajikia audax Philippi, 1887). Biodiversitas 26: 1156-1163. The digestive tract of Striped marlin (Kajikia audax Philippi, 1887): a fishery byproduct, contains several hydrolase subclass enzymes, such as protease, lipase, amylase, cellulase, and xylanase, which have practical applications in medicine, agriculture, and various industries, including pharmaceuticals, food, detergents, leather, and cosmetics. This study aimed to identify and characterize the enzymes in the digestive tract of Striped marlin. Enzymes from the hydrolase sub-class in different parts of the digestive tract, such as the stomach, pylorus, pancreas, and intestine, were analyzed separately using qualitative and quantitative methods. Each enzyme was further evaluated to determine its optimal pH and temperature. The results revealed that protease activity was the most dominant among the other enzymes. A clear zone with a diameter of >85 mm was observed on a casein substrate in the stomach and pylorus. The highest protease activity was recorded in the part of the stomach (1,044.71 U/mL): followed by the pylorus (937.21 U/mL): pancreas (492.06) U/mL, and intestine (362.21 U/mL). The optimal pH for enzyme activity was 4 in the stomach, 6 in the pylorus, 7 in the pancreas, and 10 in the intestine. The optimal enzyme activity temperature across all digestive tracts was 40?. This study provides the first comprehensive mapping of hydrolase subclass enzymes in the digestive system of Striped marlin.